Biosimilar Candidate CT-P42 in Diabetic Macular Edema: 24-Week Results from a Randomized, Active-Controlled, Phase III Study - Wolf, Sebastian; Stanga, Paulo-Eduardo; Veselovsky, Milan; Veith, Miroslav; Papp, Andras; Mange, Shobhana; Kanta Mondal, Lakshmi; Romanczak, Dominika; Janco, Ladislav; Chauhan, Rohan; Romanowska-Dixon, Bożena; Eremina, Alena; et al. (Ophthalmology. Retina, 2024)
OBJECTIVE: To demonstrate the therapeutic similarity of CT-P42 compared with reference aflibercept (Eylea) in adult patients with diabetic macular edema (DME). DESIGN: Randomized, active-controlled, double-masked, phase III clinical trial PARTICIPANTS: Patients with a diagnosis of either type 1 or 2 diabetes mellitus with DME involving the center of the macula. METHODS: Patients were randomized (1:1) to receive either CT-P42 or reference aflibercept (2 mg/0.05 ml) by intravitreal injection every 4 weeks (5 doses), then every 8 weeks (4 doses), in the main study period. Results up to week 24 are reported herein. MAIN OUTCOME MEASURES: The primary end point was mean change from baseline at week 8 in best-corrected visual acuity (BCVA) using the ETDRS chart. Equivalence between CT-P42 and reference aflibercept was to be concluded if the 2-sided 95% confidence interval (CI) (global assumptions) and 2-sided 90% CI (United States Food and Drug Administration [FDA] assumptions) for the treatment difference fell entirely within the equivalence margin of ±3 letters, as assessed in the full analysis set. RESULTS: Overall, 348 patients were randomized (CT-P42: 173; reference aflibercept: 175). Best-corrected visual acuity improved from baseline to week 8 in both groups, with a least squares mean (standard error) improvement of 9.43 (0.798) and 8.85 (0.775) letters in the CT-P42 and reference aflibercept groups, respectively. The estimated between-group treatment difference was 0.58 letters, with the CIs within the predefined equivalence margin of ±3 letters (95% CI, -0.73 to 1.88 [global]; 90% CI, -0.52 to 1.67 [FDA]). Through week 24, other efficacy results for the 2 groups, in terms of change in BCVA and retinal central subfield thickness, as well as ETDRS Diabetic Retinopathy Severity Scale score, supported therapeutic similarity. Pharmacokinetics, usability, safety (including the proportions of patients experiencing ≥1 treatment-emergent adverse event [CT-P42: 50.3%; reference aflibercept: 53.7%]), and immunogenicity were also comparable between groups. CONCLUSIONS: This study in patients with DME demonstrated equivalence between CT-P42 and reference aflibercept (2 mg/0.05 ml) in terms of efficacy, with similar pharmacokinetic, usability, safety, and immunogenicity profiles. FINANCIAL DISCLOSURE(S): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.
Keywords: Biosimilar Pharmaceuticals; vztah mezi dávkou a účinkem léčiva; Tomography, Optical Coherence; Female; Biosimilar; makulární edém; injekce intravitreální; diabetická retinopatie; výsledek terapie; ženské pohlaví; Macular Edema; Recombinant Fusion Proteins; vaskulární endoteliální růstový faktor A; Time Factors; časové faktory; optická koherentní tomografie; Diabetic macular edema; rekombinantní fúzní proteiny; lidé; Aflibercept; dvojitá slepá metoda; Angiogenesis Inhibitors; inhibitory angiogeneze; Vascular Endothelial Growth Factor A; receptory vaskulárního endoteliálního růstového faktoru; Treatment Outcome; následné studie; biosimilární léčivé přípravky; Receptors, Vascular Endothelial Growth Factor; Intravitreal Injections; CT-P42; Diabetic Retinopathy; macula lutea; Dose-Response Relationship, Drug; Male; Double-Blind Method; Follow-Up Studies; Aged; lidé středního věku; senioři; mužské pohlaví; zraková ostrost; Visual Acuity; Middle Aged; Macula Lutea; Humans